Upaya Meningkatkan Hasil Belajar Matematika Siswa Dengan Menggunakan Media Alat Peraga Konkret Pada Siswa Sekolah Dasar Kabupaten Bekasi - Yudi Budianti; Dede Abdul Azis (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
This study aims to improve mathematics learning outcomes regarding geometric material, especially cones and tubes in fifth-grade students by using concrete visual aids in learning mathematics in elementary school. The method used in this study uses Experimental Research with the flow or research design used is Quasi Experiment for data analysis using Test Trials consisting of Uni Validation, Reliability Test, Test difficulty level. Prerequisite Test consisting of Normality Test, Homogeneity Test, Hypothesis Test. Quantitative analysis and to describe the data using descriptive analysis. The results of the research based on the analysis carried out can be concluded as follows: The results of manual hypothesis testing obtained tcount = 1.876 and t (0.05; 42) = 1.682 based on the results of analysis and discussion of research data, then tcount > t (0.05;42) then HO rejected. Based on these findings, there are differences in learning outcomes between students who are taught using visual aids and students in class IV SDIT Patriot who receive traditional learning treatment. By using the NGain test, an average value of 0.770 was obtained which indicated that the success rate of students after teaching and learning was relatively high.